2017
DOI: 10.2527/tas2017.0058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of narasin (Skycis) or zinc bacitracin (Albac) inclusion on the growth performance and carcass characteristics of finishing pigs sent for slaughter using a 3-phase marketing strategy

Abstract: The objective of this study was to evaluate the effect of dietary inclusion of narasin or zinc bacitracin on the growth performance and carcass characteristics of finishing pigs sent for slaughter using a 3-phase marketing strategy. The study used 2,219 crossbred pigs in a randomized complete block design (blocking factor = start date) with 3 dietary treatments: 1) Control (no feed additive), 2) 15 mg/kg narasin (Skycis, Elanco Animal Health, Greenfield, IN), and 3) 28 mg/kg zinc bacitracin (Albac, Zoetis, Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…1 and 2, respectively. This is consistent with published research from Rickard et al (2017) that reported that 15 ppm of NAR increased carcass yield by 0.4 percentage units. Published commercial research on finishing pigs in a commercial environment using these two molecules is limited, especially among the studies that reported carcass data.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…1 and 2, respectively. This is consistent with published research from Rickard et al (2017) that reported that 15 ppm of NAR increased carcass yield by 0.4 percentage units. Published commercial research on finishing pigs in a commercial environment using these two molecules is limited, especially among the studies that reported carcass data.…”
Section: Resultssupporting
confidence: 93%
“…Past research on VIR does not indicate any effect of the antibiotic on any carcass parameter ( Castell, 1977 ). In contrast, Shircliff et al (2018) and Rickard et al (2017) reported that NAR significantly increased HCW because of greater final BW. In the studies reported herein, NAR increased carcass yield 0.5 and 0.3 percentage units versus control in Exp.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…The addition of bacitracin did not change weight gain, though it tended to improve feed intake in the current study. This result is not surprising, as growth performance enhancement by AGPs is more commonly observed in nursery pigs [ 10 , 44 ], and the grow–finish pigs in this study were raised through good barn hygiene. Nevertheless, the metabolic influences of bacitracin were still detected through fecal metabolomic analysis.…”
Section: Discussionsupporting
confidence: 65%